Protein oxidative damage and redox imbalance induced by ionising radiation in CHO cells. (3rd April 2018) - Pietraforte, Donatella; Paulicelli, Eleonora; Patrono, Clarice; Gambardella, Lucrezia; Scorza, Giuseppe; Testa, Antonella; Fattibene, Paola
Abstract: Reactive oxygen species (ROS) are important mediators of the cytotoxicity induced by the direct reaction of ionising radiation (IR) with all critical cellular components, such as proteins, lipids, and nucleic acids. The derived oxidative damage may propagate in exposed tissues in a dose- and spatiotemporal dependent manner to other cell compartments, affecting intracellular signalling, and cell fate. To understand how cell damage is induced, we studied the oxidative events occurring immediately after cell irradiation by analysing the fate of IR-derived ROS, the intracellular oxidative damage, and the modification of redox environment accumulating in Chinese hamster ovary (CHO) within 1 h after cell irradiation (dose range 0–10 Gy). By using the immuno-spin trapping technique (IST), spectrophotometric methods, and electron paramagnetic resonance (EPR) spectroscopy, we showed that IR-derived ROS (i) induced an IST-detectable, antioxidant-inhibitable one-electron oxidation of specific intracellular proteins; (ii) altered the glutathione (GSH) content (which was found to increase below 2 Gy, and decrease at higher doses, leading to a redox imbalance); (iii) decreased glutathione peroxidase and glutaredoxin activity; (iv) modified neither glutathione reductase nor thioredoxin reductase activity; (v) were detected by spin trapping technique, but adduct intensity decreased due to cell competition for ROS; and (vi) induced no EPR-detectable radicals assignable to oxidised cellular components. In conclusion, our results showed that IR generated an early high oxidising potential (protein radical intermediates, redox imbalance, modified redox enzyme activity) in irradiated cells potentially able to propagate the damage and induce oxidative modification of secondary targets.